Culture pastorale et getstion des parcaus: Observations recentesfaits en pays masai - Grandin, B.E. (1987)
Reviews the appropriateness of three major assumptions underlying pastoral development in East Africa, viz, economic irrationality of pastoralists, the unchanged nature of pastoral production systems, and the applicability of western models to pastoral development.